In-depth characterization of early stages of human induced regulatory T cell differentiation by mass cytometry - Kattelus, Roosa (My University, 2022)
Regulatory T cells (Tregs) are responsible for the maintenance of immunological homeostasis and self-tolerance. They are part of the CD4⁺ T helper (Th) cell population, but unlike other Th cells Tregs suppress immune responses by inhibiting other immune system cell responses, and function of antigen presenting cells. Tregs mediate suppression via contact dependent and humoral factor-mediated mechanisms. However, abnormalities in Treg numbers, frequencies, and suppressive function can trigger autoimmune diseases. Several therapies are under investigation to restore and enhance Tregs cell function in autoimmune diseases in vivo. On the other hand, highly activated Tregs can suppress antitumor responses, promoting cancer progression. In cancer, means to inhibit Treg function provide promising targets to control tumor cell growth. The aim of the current study was to perform an in-depth characterization of in vitro generated human induced Treg (iTreg) cell differentiation at early timepoints by high-dimensional single-cell mass cytometry. For this purpose, a panel of 25 markers was designed and validated in iTregs, differentiated in vitro from naïve human umbilical cord blood derived CD4+ T cells. The expression of these markers was further studied in iTregs compared to activated control Th0 cells over time. Additional western blot and flow cytometry analyses were performed to confirm the successful Treg differentiation by determining the Foxp3 expression. The results show an upregulation of key transcription factor Foxp3 and several co-inhibitory molecules including PD-1, CTLA-4, LAG-3 and TIM-3 were expressed and increased with time on iTregs compared to Th0 cells. In addition, surface markers like CD103, CD137, CCR4 and CXCR3, which are interesting targets in context of Treg function and diseases, showed a statistically significant upregulation on iTregs. In conclusion, this study gives insights in the regulation and cell surface marker expression of human Tregs at single cell level and opens new way to study Treg function.
Keywords: Regulatory T cell, mass cytometry, marker